Polarographic and ConductometricStudies of Uranyl Ion in Sulphuric Acid-Ethanol Media - A. Gomaa, Esam; Bekheit, G.M. (Asian Journal of Chemistry, 2010)
The polarographic behaviour of uranyl ion in sulphuric acid solutions shows three reduction waves. On adding ethanol the first wave splits into two waves and the second wave disappears, whereas the third wave disappears by increasing the percentage of ethanol in the medium. From the conductivity measurements of uranyl ion in sulphuric acid-ethanol solutions, the dissociation degrees and the association constants were calculated. The results were discussed in view of the solvation volumes and the free energies of solution.